2003
DOI: 10.1002/jcu.10136
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic measurements of normal gallbladder sizes in children

Abstract: Values for the size of the normal pediatric gallbladder are defined and will be helpful in the diagnosis of gallbladder abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
(8 reference statements)
1
9
0
1
Order By: Relevance
“…The body surface area showed positive association with the width and volume of the gall bladder from this study, which agreed with the study performed by Ugwu 3 in 2007 and also several other studies. [10][11][12][13][14][15] Present study established that there is no significant difference in mean gall bladder-volume and wall thickness compared with other research works. The pattern of correlation between gall bladder-volume and demographic parameters, however, tend to vary among different studies.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The body surface area showed positive association with the width and volume of the gall bladder from this study, which agreed with the study performed by Ugwu 3 in 2007 and also several other studies. [10][11][12][13][14][15] Present study established that there is no significant difference in mean gall bladder-volume and wall thickness compared with other research works. The pattern of correlation between gall bladder-volume and demographic parameters, however, tend to vary among different studies.…”
Section: Discussionmentioning
confidence: 63%
“…This study showed weight and BSA positively correlated with the width, height and volume of the gall bladder. Yoo et al, 14 and Sari et al, 9 also showed a positive correlation between subject weight and gall bladder-volume among Asians. Present study didn't display any relationship between BMI and gall bladder length, width, height and volume, hence it concurrent with the study done by Caroli-Bose et al 7 However another study by Ugwu 3 in 2007 showed a relationship between BMI and gall bladder-volume.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…De forma similar ao observado no presente estudo, Yoo et al (2003) encontraram correlação positiva e significativa entre comprimento e largura da vesícula biliar com o peso de crianças submetidas ao exame ultrassonográfico. Como a secreção da bile é contínua (Sohn & Couto 2012) e hormônios como gastrina e secretina não parecem afetar a produção da bile no coelho, como ocorre em cães e gatos (Shaw & Heath 1974), o peso corporal no coelho pode ser o fator com maior influência no tamanho da vesícula biliar.…”
Section: Quadro 6 Média E Desvio Padrão Do Volume (Cm 3 ) Renal Direunclassified
“…Surgical consultation was obtained and agreed with this preliminary diagnosis, pending further imaging data to better define GB presence and location, and possible pancreatobiliary junction abnormalities. Magnetic resonance imaging (3 T, Magnetom Trio, Siemens Erlangen, Germany) showed the suspected "choledochal cyst" to actually be a voluminous saccular GB, 5 to 10 times larger than normal (105 × 40 mm; V = 101.7 cm 3 ) (normal value for age 56 ± 8 × 19 ± 4 mm, V = 11.5 ± 5.3 cm 3 ) [7]. The dilated infundibular region of the GB reached the porta hepatis indenting the junction, displacing it behind the bile duct.…”
mentioning
confidence: 99%